PI3K/AKT signaling mediates stress-inducible amyloid formation through c-Myc - Emma Lacroix; Evgenia A. Momchilova; Sahil Chandhok; Mythili Padavu; Richard Zapf; Timothy E. Audas (Cell Reports)
Summary: In response to environmental stress, eukaryotic cells reversibly form functional amyloid aggregates called amyloid bodies (A-bodies). While these solid-like biomolecular condensates share many biophysical characteristics with pathological amyloids, A-bodies are non-toxic, and they induce a protective state of cellular dormancy. As a recently identified structure, the modulators of A-body biogenesis remain uncharacterized, with the seeding noncoding RNA being the only known regulatory factor. Here, we use an image-based high-throughput screening approach to identify candidate pathways regulating A-body biogenesis. Our data demonstrate that the phosphatidylinositol 3-kinase (PI3K)/AKT signaling axis meditates A-body formation during stress exposure, with AKT activation repressing glycogen synthase kinase-3 (GSK3)-mediated degradation of c-Myc. This enhances c-Myc binding to regulatory elements of the seeding noncoding RNA, upregulating the transcripts that nucleate A-body formation. Identifying a link between PI3K/AKT signaling, c-Myc, and physiological amyloid aggregates extends the range of activity for these well-established regulators while providing insight into cellular components whose dysregulation could underly amyloidogenic disorders.